Outer membrane vesicles extracted from Neisseria meningitidis serogroup X for prevention of meningococcal disease in Africa. (July 2017) - Acevedo, Reinaldo; Zayas, Caridad; Norheim, Gunnstein; Fernández, Sonsire; Cedré, Barbara; Aranguren, Yisabel; Cuello, Maribel; Rodriguez, Yaimara; González, Humberto; Mandiarote, Aleida; Pérez, Marylin; Hernández, Maritza; et al.
Graphical abstract: Abstract: Meningococcal disease is caused mainly by serogroups A, B, C, Y, W of N. meningitidis . However, numerous cases of meningitis caused by serogroup X N. meningitidis (MenX) have recently been reported in several African countries. Currently, there are no licensed vaccines against this pathogen and most of the MenX cases have been caused by meningococci from clonal complex (c.c) 181. Detergent extracted meningococcal outer membrane vesicle (dOMV) vaccines have previously shown to be safe and effective against epidemics of serogroup B meningococcal disease in all age groups. The aim of this work is therefore to obtain, characterize and evaluate the vaccine potential of dOMVs derived from a MenX strain (OMVx). Three experimental lots of OMVx were prepared by deoxycholate extraction from the MenX strain BF 2/97. Size and morphology of the vesicles was determined by Dynamic Light Scattering and electron microscopy, whereas the antigenic composition was characterized by gel electrophoresis and immunoblotting. OMVx were thereafter adsorbed to aluminium hydroxide (OMVx/AL) and two doses of OMVx were administered s.c. to groups of Balb/c mice three weeks apart. The immunogenicity and functional antibody activities in sera were evaluated by ELISA (anti-OMVx specific IgG responses) and serum bactericidal activity (SBA) assay. The size range of OMVx was shown to be between 90 and 120 nm, whereas some of the antigens detected were the outer membrane proteins PorA, OpcA and RmpM. The OMVx/AL elicited high anti-OMVx antibody responses with bactericidal activity and no bactericidal activity was observed in the control group of no immunised mice. The results demonstrate that OMVx are immunogenic and could form part of a future vaccine to prevent the majority of meningococcal disease in the African meningitis belt.